ANALISIS PENTAD DRAMATISME KONTEN YOUTUBE AHMAD DHANI TENTANG HAK CIPTA DALAM KONFLIK DENGAN ONCE MEKEL - Rijanto Witjaksono; Ahmad Setyono (Jurnal Komunikasi & Media Digital, 2024)
This research examines the use of the YouTube account "Ahmad Dhani in the News" as a means of rhetorical communication in the conflict regarding copyright between Ahmad Dhani and Once Mekel. This research mainly analyzes how Ahmad Dhani uses social media to convey persuasive messages, summons, and mediate about the conflict. Apart from that, this research also applies pentad drama studies to understand how drama elements such as actors, action, and setting are used in Dhani's video content to strengthen the narrative and arguments conveyed. The research results show that Dhani strategically utilizes rhetorical techniques to shape public opinion and clarify his position in the conflict, while the dramatic structure in his podcast strengthens the dramatic impression and his role in the narrative. These findings are expected to provide insight into the dynamics of digital communication in copyright conflicts as well as the dramatic strategies used in social media.